Scalable, Opportunistic, Energy Efficient Routing (SOEER) - A Novel Clustering Approach for Wireless Sensor Networks - Poornachander, V.; Dhanalaxmi, V. (2022 International Conference on Applied Artificial Intelligence and Computing (ICAAIC), 2022)
The small size of batteries used by Wireless Sensor Networks (WSNs) is the important constraints of WSNs. Clustering is one technique for routing. The energy consumption of sensor nodes is lowered using this technology. In sensor networks, routing issues are handled by the organization layer. The huge quantity of energy required to transmit and gather radio signals makes power a significant factor to examine. Therefore, WSNs play a crucial role in preserving the environment. In progressing research, routing practices are being designed so that less power is required for correspondence, thus expanding the lifecycle of the network. It is excessively costly to replace the vitality in the majority of applications. A description of vitality-effective routing is presented in this paper. Cluster head (CH) nodes are selected randomly in a cyclical manner by the LEACH protocol. Choosing the low energy node as CH may result in instability within the network. If the cluster size is too large or too small, it will affect the network's survival time. This problem has been addressed with a new solution. A new clustering algorithm Scalable, Opportunistic, Energy Efficient Routing (SOEER) presented in this paper, for improving the energy efficiency, life time, Packet Delivery Ratio and throughput of network. During data transmissions, each node transmits a single hop transmission to the CH and the CH transmits multiple hops to the BS. This research study finds that extending the network utilization effectively will only consume less energy. A recommended clustering method considers the congestion situation in order to optimize the network topology and select more suitable nodes for CH.